ASSOCIATION OF PARENTAL BEHAVIOR IN CHOOSING SNACKS WITH NUTRITIONAL STATUS OF SCHOOL-AGE CHILDREN AT SDN MOJOLANGU 4 - Dera, Desembriani Natasya; Dewi Satiti, Ika Arum; Jayanti, Nicky Danur; Harnawati, Riska Arsita (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
Parents' behavior in selecting snacks significantly influences children's snacking habits, which are positively associated with nutritional status. The nutritional status of school-age children is influenced by several factors, including their daily eating habits at home instilled by their parents and peer-snacking behavior in the school environment. This study investigated the relationship between parents' behavior in snack selection and the nutritional status of school-age children at SDN 4 Mojolangu. The research employed an analytical correlational design with 160 respondents comprising 80 parents and 80 students in grades 1-4. Additionally, weight and height measurements were taken for the students. Statistical analysis was conducted using the Sommers'D test. The results indicate a significant relationship between parents' behavior in snack selection and the nutritional status of school-age children. The analysis of the correlation between parental behavior and nutritional status (BMI-for-age) yielded a significance value of p=0.000 (r=1.000), indicating a strong positive correlation. Meanwhile, the correlation between nutritional status (Height-for-age) showed a significance value of p=0.000 (r=0.654), demonstrating a strong positive correlation.